A Theology for the Church - Akin, Daniel L.; George, Timothy; Moore, Russell; Patterson, Paige; Mohler, Albert; Dever, Mark. (Nashville : B & H Publishing Group, 2014)
The revised edition of A Theology for the Church retains its original structure, organized under these traditional theological categories: revelation, God, humanity, Christ, the Holy Spirit, salvation, the church, and last things. Each chapter within these sections contains answers to the following four questions: What does the Bible say? What has the church believed? How does it all fit together? How does this doctrine impact the church today? Contributions from leading Baptist thinkers R. Albert Mohler, Jr., Paige Patterson, and Mark Dever among others will also a.
Chapter 10: The Work of Christ 439Chapter 11: The Person and Work of the Holy Spirit 483; The Doctrine of the Holy Spirit 481; Chapter 12: The Work of God: Salvation 543; The Doctrine of Salvation 541; Chapter 13: The Church 603; The Doctrine of the Church 601; Chapter 14: Personal and Cosmic Eschatology 671; The Doctrine of Last Things 669; Conclusion 723; Name Index; Scripture Index.
Print version record.
Keywords: Religion; Theology, Doctrinal; Theology; Theology, Doctrinal; Baptists -- Doctrines; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books